The predictive value of uvulo-palatoglossal junctional ulcers as an early clinical sign of exanthem subitum due to human herpesvirus 6 - Chua, K.B.; Lam, S.K.; AbuBakar, Sazaly; Lim, S.T.; Paranjothy, M.; Koh, M.T.; Lee, W.S. (2000)
Background: The clinical sign of uvulo-palatoglossal junctional (UPJ) ulcers was first noted in 1983 in a 5.5-month-old baby with exanthem subitum (ES). An earlier prospective clinical study showed that there was a strong association of UPJ ulcers and occurrence of ES with a positive predictive value of 95.3 and negative predictive value of 100. Objective: To determine the value of uvulo-palatoglossal junctional (UPJ) ulcers as an early clinical sign of exanthem subitum (ES) due to human herpesvirus 6 (HHV 6) infection. Study? design: A case-control study of 20 febrile children with UPJ ulcers versus 26 febrile children without UPJ ulcers. These children were followed up for any development of ES and investigated for human herpesvirus 6 (HHV 6) as the causative agents of the febrile episodes. Results: In this study, 20 out of 46 febrile children aged 3 months to 3 years with UPJ ulcers were virologically and/or serologically confirmed to be due to primary HHV 6 infection. The rest of the 26 children without ulcers did not have HHV 6 infection. Of the 20 children with UPJ ulcers, only 17 of the 19 children with adequate follow-up till subsidence of fever developed ES. None of the 26 children without UPJ ulcers developed ES. Conclusion: Statistically, then was a significant association of UPJ ulcers as an early sign of ES with a positive predictive value of 89.5 and negative predictive value of 100. This finding also suggests that the presence of UPJ ulcers is a useful pathognomic clinical sign of symptomatic primary HHV 6 infection. (C) 2000 Elsevier Science B.V. All rights reserved.